The Effect of Electrode Gap Distance on Brown's Gas - Tria Puspa Sari; Denny Widhiyanuriyawan; Radissa Dzaky Issafira; Wahyu Dwi Lestari; Ndaru Adyono; Wiliandi Saputro; Ahmad Khairul Faizin (Nusantara Science and Technology Proceedings)
The electrolysis of water is one of many methods to produce hydrogen by converting electrical and thermal energy into hydrogen and oxygen. In this study, a generator of the HHO dry cell type is used to produce brown gas. Brown’s gas consists of two hydrogens and one oxygen or Oxyhydrogen (HHO). Observation will be conducted to obtain the effect of electrode gap distance to increase the productivity of Brown’s Gas with a mixture of 2500 ml pure water and catalyst of NaHCO3. The results show that if the electrode gap is small, it will produce more brown gas than the long gap. However, research still needs to be done on how close the electrode gap distance is needed to produce maximum brown gas.